A simulation study of non-linear disturbance observer-based sliding mode control for inverted pendulum with mismatched disturbances. (2015) - Tandon, Bhawna; Narayan, Shiv; Kumar, Jagdish
The work presented here is concerned with the robust control problem for the inverted pendulum with mismatched disturbances via a non-linear disturbance observer (NDO)-based sliding mode control (SMC) method. The NDO-based SMC method provides a solution to the main limitation of conventional first-order sliding mode controllers that is the presence of high frequency oscillations in the control input known as chattering while retaining the nominal performance. To show the effectiveness of NDO-based SMC, both the conventional SMC and the integral SMC (I-SMC) methods are employed in the simulation studies for the purpose of comparison studies and results demonstrate the merits of NDO-based SMC.